Students’ Perception Between Distance Learning and Classroom Learning at English Education Study Program of STKIP PGRI Lubuklinggau - Ummi Azzara Zuztra; Ayu Oktaviani; Maria Ramasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The problem of the research is: “How are the students’ perception between distance learning and classroom learning at English Education Study Program of STKIP PGRI Lubuklinggau”. The objectives of the research were to find out and to describe Students’ perceptions about distance learning and classroom learning at English Education Study Program of STKIP PGRI Lubuklinggau. The sample was 30 students of English Education Study Program. The samples were taken through stratified random sampling. The researcher used a survey research, and the data were collected by using questionnaire and interview. Techniques for analyzing the data used simple basic statically techniques. The data were score by using Likert Scale. The result of the research was the students studied negative and positive with distance learning; students cannot handle the whole material perfectly because distance learning was signals of phone and the mobile data, they had a flexibility in taking time on work. They more understanding the material when they used technology. Besides, in the result studied negative and positive of classroom learning; the time and energy that is used more in learning activities. They had better interaction between students and lecture because learning in class interaction between lecturers and students is closer both emotionally and verbally. Keywords: Classroom Learning, Distance Learning, Students’ Perception